Intravenous Reelin rescues despair-like behavior, Reelin cells in the dentate sub-granular zone, and spleen atrophy in the cyclic corticosterone model of recurring depressive episodes - Reive, B. S.; Johnston, J.; Sánchez-Lafuente, C. L.; Scheil, Kaylene; Kurz, K.; Kalynchuk, L. E.; Caruncho, H. J. (Frontiers in Pharmacology, 2024)
Novel antidepressants are predominantly evaluated preclinically in rodent models of chronic stress in which animals experience a single prolonged exposure to chronic stress prior to treatment. Rodent models of a single episode of chronic stress translate poorly to human depressive disorders which are commonly marked by recurring depressive episodes. Intravenous administration of Reelin has previously been shown to resolve immobility in the forced swim test in rats exposed to a single prolonged exposure to chronic stress. To determine whether Reelin has antidepressant-like properties in a model of recurring depressive episodes, Long Evans rats (N=57) were exposed to multiple cycles of chronic stress and stress-free periods before administration of a single injection of Reelin during the final cycle of chronic stress. Animals then performed in the forced swim test and the open field test before post-mortem evaluation of Reelin cell counts in the sub-granular zone of the dentate gyrus to determine the impact of treatment on hippocampal Reelin levels and spleen white pulp to evaluate the role of Reelin treatment in peripheral inflammation. Results show a single Reelin injection reversed elevated levels of immobility in the forced swim test in both males and females exposed to the cyclic chronic stress model of recurring depressive episodes. Treatment with Reelin also restored Reelin positive cell counts in the dentate gyrus sub-granular zone and reversed atrophy of spleen white pulp. The results shown here indicate treatment with Reelin could effectively resolve alterations to forced swim test behaviour caused by the cyclic corticosterone model of recurring depressive episodes and that Reelin homeostasis is important for regulating stress-related inflammation. Future preclinical antidepressant research should incorporate models of multiple depressive episodes to improve the translation of preclinical rodent research to human depressive disorders.